2016
DOI: 10.1080/01480545.2016.1174870
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytogenetic and DNA damage induced by the antidepressant drug-active ingredients, trazodone and milnacipran,in vitro

Abstract: Trazodone and milnacipran are the active antidepressant drugs that are being used in the treatment of psychiatric disorders. In this study, the in vitro genotoxic effects of trazodone and milnacipran have been determined in human peripheral blood lymphocytes by using chromosomal aberrations (CAs), sister chromatid exchanges (SCEs), micronuclei (MN), and comet assays. 3.13; 6.25; 12.50; 25.00; 50.00; and 75.00 μg/mL concentrations of trazodone and 2.50; 5.00; 10.00; 20.00; 30.00; and 40.00 μg/mL concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…80 83 Comet, micronucleus, chromosomal aberration, and sister chromatid exchange assays are commonly used to determine the mutagenic and genotoxic effects induced by xenobiotics. 84 87 Although studies are insufficient to investigate the genotoxic effects of TRZ, it has been shown that trazodone have clastogenic and mutagenic effects on human lymphocytes in vitro. 85 According to the results of our study, there was a significant increase in tail moment indicating DNA damage in TRZ-administered rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 83 Comet, micronucleus, chromosomal aberration, and sister chromatid exchange assays are commonly used to determine the mutagenic and genotoxic effects induced by xenobiotics. 84 87 Although studies are insufficient to investigate the genotoxic effects of TRZ, it has been shown that trazodone have clastogenic and mutagenic effects on human lymphocytes in vitro. 85 According to the results of our study, there was a significant increase in tail moment indicating DNA damage in TRZ-administered rats.…”
Section: Discussionmentioning
confidence: 99%
“…84 87 Although studies are insufficient to investigate the genotoxic effects of TRZ, it has been shown that trazodone have clastogenic and mutagenic effects on human lymphocytes in vitro. 85 According to the results of our study, there was a significant increase in tail moment indicating DNA damage in TRZ-administered rats. Besides, increasing oxidative stress in cardiac tissue may induce structural changes such as cardiomyopathy, cardiac hypertrophy, and dysfunction of contractile protein.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we detected the induction of DSBs in MDA-MB-231 cells by neutral comet assays and confocal immunofluorescence assays, stained with DSB biomarker γH2AX . Part A of Figure shows that TA12 significantly increased the generation of endogenous DSBs in MDA-MB-231 cells, as indicated by the statistical increase in olive tail moment . The percentages of γH2AX focal positive cells were obviously increased in MDA-MB-231 cells treated with different concentrations of TA12 (0, 10, and 20 μM).…”
Section: Resultsmentioning
confidence: 94%
“…41 Part A of Figure 7 shows that TA12 significantly increased the generation of endogenous DSBs in MDA-MB-231 cells, as indicated by the statistical increase in olive tail moment. 42 The percentages of γH2AX focal positive cells were obviously increased in MDA-MB-231 cells treated with Reactive oxygen species (ROS) plays an important role in the induction of DNA damage. 43 We speculated the possibility that overproduced ROS induced by TA12 entered into nucleus to enhance ROS-mediated DNA damage.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…SNRIs such as duloxetine and milnacipran were found to have genotoxic and cytotoxic effects in different test systems [51]. Duloxetine ranks first for hyponatremia, severe skin reactions and life-threatening liver injury [52], but citalopram or escitalopram ranks first for cardiovascular complications.…”
Section: Other Side Effects Of Antidepressantsmentioning
confidence: 99%